Fatal case of ciprofloxacin-induced toxic epidermal necrolysis - Mishra, Adesh D.; Urade, Prashant M.; Mittal, Niti; Gupta, M. C. (International Journal of Basic & Clinical Pharmacology, 2017)
Ciprofloxacin is a very commonly used antibiotic. Mild to moderate gastrointestinal side effects commonly reported whereas serious reactions such as Steven–Johnson syndrome and toxic epidermal necrolysis (TEN) are very rare. We report the fatal case of 25 years female who had TEN after ingestion of tablet ciprofloxacin. This case report highlights the need to be critically aware of this rare, but life-threatening side effect of this commonly prescribed antibiotic.